Bibliometric Analysis of Local Food Security Research in Southeast Asia with a Focus on Research Issues, Collaboration, and Future Agenda - Loso Judijanto (West Science Agro, 2026)
This study aims to map and analyze the development of local food security research in Southeast Asia through a bibliometric approach, with a focus on identifying dominant research issues, collaboration patterns, and future research directions. Using data extracted from the Scopus database and analyzed with VOSviewer, the study examines publication trends, keyword co-occurrence networks, overlay visualization, and density mapping. The findings indicate that food security research in Southeast Asia is strongly centered on themes such as food supply, climate change, sustainable development, and agricultural production. Over time, the research focus has shifted from macro-level production and economic perspectives toward resilience-based and sustainability-oriented frameworks, particularly emphasizing smallholder vulnerability, crop yield under climate stress, and adaptive agricultural strategies. The density analysis further reveals that while core themes are well established, topics related to localized governance, protein diversification, urban food systems, and digital innovation remain less explored. Collaboration patterns suggest regional anchoring with connections to broader developing-country discourse, highlighting the importance of strengthening intra-regional research networks. The study provides a structured overview of the intellectual landscape of local food security research in Southeast Asia and offers a forward-looking agenda emphasizing climate resilience, sustainability integration, and inclusive regional collaboration.